The Philosophy of character house as islamic character building laboratory: A SWOT analysis - Musadad Ahmad; Nahidloh Shofiyun; Nasik Khoirun; Pujiati Tri (BIO Web of Conferences)
This research was conducted as an effort to solve the students’ problem related their cultural shock of Islamic values during face-to-face class after pandemic era caused of Covid 19. This study will investigate the formation of character house in Islamic faculty which provides distinctive Islamic values that are different from other institutions. The research method used is descriptive qualitative with data collection through observation, in-depth interviews, and documentation studies. SWOT analysis was used to identify internal and external factors that affect the effectiveness of Character House in achieving its goals. The results showed that the main strengths of the Character House lie in the comprehensive curriculum, full support from the faculty, and adequate facilities. However, there are weaknesses in the form of lack of active student involvement and suboptimal teaching resources. In terms of opportunities, the Character House has the potential to collaborate with various external institutions and utilize digital technology in the character building process. However, threats from the negative influence of social media and a less conducive external environment are challenges that need to be overcome. This study gives a new recommendation for character house by giving the strategic and prudent utilization of digital technology is proposed. It is expected that the Character House of the Islamic Faculty can be an effective laboratory model in shaping a generation with excellent Islamic character and contributing positively to society.